Doctoral Education as a Practice of Adult Education - Dianne Ramdeholl; Tom Heaney (Adult Education Research Conference, 2017)
This presentation features chapter authors from the recently published New Directions of Adult and Continuing Education "Reimaging Doctoral Education as a Practice of Adult Education."
Keywords: doctoral education; adult education; participatory practices